Italian Teen Stars During the Pandemic: a Case Study of SKAM Italia's Actors - Maria Elena Alampi (Cinergie, 2022)
Italian teen movies have rarely been recognized by critics as socially engaged because they are aimed at a teenage audience and are seen to favour sentimental plots (O’Rawe 2020). Nonetheless, products broadcast on online platforms (such as Amazon Prime and Netflix) are changing this by combining consumer media formulas with various socio-political themes. Above all, digitalization has made these issues more accessible and spread the image of teen stars to an ever-expanding audience on numerous social networks. However, what has happened since the beginning of the pandemic in Italy? The Italian celebrities involved in March 2020 in the #IoRestoACasa campaign contributed to raising public awareness of Covid-19 prevention (Vogue Italia 2020). This article will focus on the commitment of the young actors in SKAM Italia (2018-in production) through the #IoRestoACasa and Su la Maschera giù i contagi campaigns aimed at younger audiences. The article will examine the social media content of actors in the SKAM Italia series, arguing that the voices of young celebrities were important in normalizing the practice of “staying at home” and wearing a mask to mitigate the spread of the virus.